“I am sick, but that’s not all that I am”: patient perspectives on psychological adaptation over time to inborn errors of immunity - Breanna J. Beers; Hannah R. Davidson-Swinton; Katie L. Lewis; Michael R. Setzer; Magdalena A. Walkiewicz; Morgan N. Similuk (Journal of Community Genetics, 2025)
Inborn errors of immunity (IEI) are rare heritable disorders of the immune system predisposing to atypical infections, autoimmunity, inflammation, and risk of malignancy. Adaptation is the process of incorporating stressful experiences into one’s life; these experiences may include onset of illness, receiving a diagnosis, or suffering without a diagnosis. Poor adaptation is linked to adverse outcomes including psychiatric comorbidities and decreased well-being. Most people with chronic illnesses and rare diseases adapt to their condition with time, but little is known about how this happens. We seek to address this gap in knowledge by investigating features of successful adaptation to IEI over time to help providers facilitate this process among those who struggle. We interviewed 20 self-reportedly well-adapted adults with IEI about their experiences of adaptation. We identified three overarching themes. First, many participants grappled with shame and loss but ultimately integrated their illness into their lives through acceptance, gratitude, and self-compassion. Second, knowledge and choice contributed to participants’ perceived control, but most participants were also forced to acknowledge the limits of that control when confronting unpredictable symptoms. Finally, social relationships could influence adaptation either positively or negatively. Notably, many participants found meaning in giving back to their communities, especially by educating others about their condition. Ultimately, participants showed that adaptation to life with IEI is complex and ongoing, requiring frequent recalibration to emerging challenges in new life stages. We provide recommendations to providers to help the results of this study shape their discussions with patients.

Perceived control is significantly associated with psychological adaptation in individuals with known or suspected inborn errors of immunity - Michael Setzer; Jia Yan; Lori Erby; Morgan Similuk (Journal of Community Genetics, 2023)

Correction to: Understanding the phenotypic spectrum and family experiences of XYY syndrome: Important considerations for genetic counseling - Colleen Jodarski; Rylee Duncan; Erin Torres; Rachel Gore; Armin Raznahan; Morgan Similuk (Journal of Community Genetics, 2023)

Understanding the phenotypic spectrum and family experiences of XYY syndrome: Important considerations for genetic counseling - Colleen Jodarski; Rylee Duncan; Erin Torres; Rachel Gore; Armin Raznahan; Morgan Similuk (Journal of Community Genetics, 2023)
XYY syndrome is characterized by a variable neurodevelopmental phenotype, with features including developmental delays, cognitive impairments, and an increased risk for mental health conditions. There are two recent developments that have primarily motivated this review. The first is the increased use of non-invasive prenatal screening (NIPS), which will likely result in more individuals being diagnosed with XYY prenatally. As such, health care providers (HCPs) both within genetics and outside of the specialty are more likely to encounter this diagnosis in the future. The second is advances in the understanding of the phenotypic variability of XYY through biobank and deep phenotyping efforts. As the phenotypic spectrum of XYY syndrome continues to expand, families will face greater uncertainty when receiving this diagnosis. Given both of these developments, HCPs will need to have up-to-date and accurate information about XYY to better counsel families. Furthermore, the ability to employ effective counseling techniques, such as anticipatory guidance, will aid in supporting and guiding families through the diagnostic journey. This review aims to provide insight on the neurodevelopmental and psychosocial aspects of XYY syndrome by discussing current research and borrowing from the relevant psychosocial literature of other genetic conditions. In this way, we hope to equip HCPs with the ultimate goal of improving the care and support provided to individuals with XYY and their families.

Patient and genetic counselor perceptions of in-person versus telephone genetic counseling for hereditary breast/ovarian cancer - Aryana S. Jacobs; Marc D. Schwartz; Heiddis Valdimarsdottir; Rachel H. Nusbaum; Gillian W. Hooker; Tiffani A. DeMarco; Jessica E. Heinzmann; Wendy McKinnon; Shelley R. McCormick; Claire Davis; Andrea D. Forman; Alexandra Perez Lebensohn; et al. (Familial Cancer, 2016)